Effects of Temperature and Water Availability on Northern European Boreal Forests - Ruiz-Pérez, Guiomar; Vico, Giulia (Frontiers in Forests and Global Change, 2020)
Boreal forests are warming twice as fast as the rest of the planet. Do the benefits of higher temperatures and longer growing seasons for forest productivity exceed the negative effects of more frequent dry spells and heat waves, shifting precipitation patterns and higher evaporative demands? And are the effects uniformly distributed geographically? To answer to these questions, we use NDVI as a proxy of forest productivity and explore, via Partial Least Square (PLS) regression analyses, the relation between climatic variables and forest productivity at the regional scale. We focus on Northern Europe, a region for which contrasting findings on the effects of warming have been reported and that has so far been overlooked by systematic large-scale explorations of the linkages between boreal forest productivity and climatic conditions. Our results show that the effects of warmer temperatures on boreal forest productivity are not uniformly positive and that water stress is already negatively affecting the productivity of these forests. Indeed, increased temperatures appear beneficial in northern and wetter regions, while warmer temperatures mostly reduce forest productivity in southern and drier areas. These results are suggestive of already existing limitations due to water availability and warm temperatures, even in mesic regions like Northern Europe. These conditions are expected to become more frequent and intense in the future, potentially reducing the ability of boreal forests to provide their essential ecosystem services unless forest management practices are adapted to the new conditions.